Analysis of potentials and problems of dairy farming in North Bihar - KESHAVA, KESHAVA; MANDAPE, M K (The Indian Journal of Animal Sciences, 2014)
The study was carried out to analyse problems in and prospects of dairy farming in Muzaffarpur District of north Bihar. Farmers (100) belonging to different landholding categories and rearing at least 1 milch animal were randomly selected as respondents. The result of the study revealed that dairy farming in the area was characterized by inadequate herd size, low milk productivity and poor feeding practices. The major problems faced by farmers in dairy farming were proneness of animals to discases, costly cattle feeds and unavailability of veterinary facilities and regular milk market.